Cardiac Aging: From Basic Research to Therapeutics. (10th March 2021) - Yan, Mingjing; Sun, Shenghui; Xu, Kun; Huang, Xiuqing; Dou, Lin; Pang, Jing; Tang, Weiqing; Shen, Tao; Li, Jian
Abstract : With research progress on longevity, we have gradually recognized that cardiac aging causes changes in heart structure and function, including progressive myocardial remodeling, left ventricular hypertrophy, and decreases in systolic and diastolic function. Elucidating the regulatory mechanisms of cardiac aging is a great challenge for biologists and physicians worldwide. In this review, we discuss several key molecular mechanisms of cardiac aging and possible prevention and treatment methods developed in recent years. Insights into the process and mechanism of cardiac aging are necessary to protect against age-related diseases, extend lifespan, and reduce the increasing burden of cardiovascular disease in elderly individuals. We believe that research on cardiac aging is entering a new era of unique significance for the progress of clinical medicine and social welfare.